Team-based learning versus traditional lectures in local anesthesia course: A cross-sectional study exploring dental students’ perception and performance - Salah Sakka (Saudi Journal of Anaesthesia)
Background: Team-based learning (TBL) as a student-centered approach can be encouraged and supported by transforming the conventional lecture format into an engaging and active process of learning. The objective of this study was to explore students’ perception of team-based learning and compare their performance after TBL sessions and traditional lectures in the local anesthesia course. Materials and Methods: Eight topics of local anesthesia during the academic years 2022–2023 and 2023–2024 were divided into team-based learning sessions and traditional lectures. Teaching activities in TBL included tests and group discussions. A cross-sectional descriptive questionnaire comprising 10 written questions targeting students’ perception of TBL and traditional lectures was handed to students at the end of the course. Results: The mean average scores of responses agreed with the related questions’ statements. The results of Pearson’s correlation test revealed that there was a significant relationship (r = 0.780, P < 0.05) between the statements of teaching methods and student’s responses in both academic years. Conclusion: Students performed better and had positive opinions of TBL as their preferred learning technique when team-based learning substituted some didactic lectures.